A influência do treinamento na redução de erros no uso de equipamentos médicos hospitalares - CABRAL, Évany Ferreira (2025)
This study examines the influence of continuous training on reducing errors in the use of hospital medical equipment, emphasizing the importance of healthcare professional trainingto ensure patient safety and equipment efficiency. The integrative literature review shows that inadequate training is directly linked to operational failures, compromising the availability andperformance of medical devices. The research also explores the application of Brazilianstandards, such as NBR ISO 10015 and NBR 15943:2011, which standardize technical trainingprocesses, as well as teaching technologies and planning methodologies like the PDCA, LCM and cycle FMEA. These tools contribute to the continuous improvement of device operation and thereduction of incidents. It concludes that structured training programs and constant evaluations are essential to minimize errors and optimize equipment use in clinical environments